DHA-PC protects kidneys against cisplatin-induced toxicity and its underlying mechanisms in mice. Issue 3 (26th February 2019) - Shi, Hao-Hao; Wang, Cheng-Cheng; Guo, Ying; Xue, Chang-Hu; Zhang, Tian-Tian; Wang, Yu-Ming
Abstract : DHA-PC protected the kidney against cisplatin-induced toxicity through sirtuin 1 activation, the inhibition of oxidative stress and apoptosis. Abstract : Cisplatin is an effective chemotherapeutic agent used in the treatment of various cancers. However, its use is usually complicated by nephrotoxic side effects, which limit its clinical application. Interestingly, DHA supplementation has been found to exhibit anticancer activity without any side effects. It is noted that DHA-PC has been applied in the treatment of kidney diseases. Our aim in the current study was to investigate whether DHA-PC treatment could alleviate cisplatin-induced nephrotoxicity using a Balb/c mice model. Our results showed that DHA-PC could significantly prolong the survival time, while the traditional DHA had no remarkable changes. In addition, short supplements of DHA-PC alleviated the cisplatin-induced kidney dysfunction, such as increased levels of blood urea nitrogen and creatinine. DHA-PC could protect the kidneys against cisplatin-induced toxicity, which might be attributed to the sirtuin 1 activation and the inhibition of oxidative stress and apoptosis. These findings suggest that DHA-PC might be a new dietary strategy for the treatment of nephrotoxicity.